Experiencing Passion as an "essentia vitae" of Educational Biographies of Eminent Musicians From Cracow - Iwona Czaja-Chudyba; Monika Kowalska (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: The aim of the paper was to discuss a function of passion in professional personal lives of eminent Cracow musicians. THE RESEARCH PROBLEM AND METHODS: The paper raises the problem of the role of passion in the process of shaping musical eminence, answers the question of the scope of experiencing it as well as it manifesting in activities of outstanding individuals. In conducted research and interpretations, the qualitative perspective and biographical method were applied. The leading technique was problem-concentrated qualitative interview, partially structured, carried out with ten eminent instrumentalists. THE PROCESS OF ARGUMENTATION: The theoretical basis for this reading of the experience of educational biographies was provided by the Model of Authentic Vocation of J. Weller and the Dualistic Model of Passion of A. Bonneville-Roussy, G. Lavigne and R. Vallerand. The interpretations of the research material described the topography of experiencing passion. RESEARCH RESULTS: The article describes autonomous passion associated with musical mastery, instrumental motivation to practice, as well as distinguishes important factors that determine the experience of passion, persistence or burnout (tenacity, ambition, community transfer, conflict of motives, work overload), and concretizes the qualities of musical passion of outstanding musicians: professionalization, love of music, integrity, creativity, strength and determination in pursuit of goals, as well as humility in the face of challenges. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: Deciphering the senses and meanings that prominent Cracow musicians attributed to passion suggests that it was autonomous, harmonious and instrumental, motivated by the pursuit of mastery, and that the trajectories of the musicians' professional biographies were a manifestation of a "professionalization of passion," which formed the core of their educational experience and constituted and defined their life creed.